Convergence in National Alcohol Consumption Patterns: New Global Indicators*. (18th August 2017) - Holmes, Alexander J.; Anderson, Kym
Abstract: With increasing globalisation and interactions between cultures, countries are converging in many ways, including in their consumption patterns. The extent to which this has been the case in alcohol consumption has been the subject of previous studies, but those studies have been limited in scope to a specific region or group of high-income countries or to just one or two types of alcohol. The present study updates earlier findings, covers all countries of the world since 1961, and introduces two new summary indicators to capture additional dimensions of the extent of convergence in total alcohol consumption and in its mix of beverages. It also distinguishes countries according to whether their alcoholic focus was on wine, beer, or spirits in the early 1960s as well as their geographic regions and their real per-capita incomes. For recent years, we add expenditure data and compare alcohol with soft drink retail expenditure, and we show the difference it makes when unrecorded alcohol volumes are included as part of total alcohol consumption. The final section summarizes our findings and suggests that further research could provide new demand elasticity estimates and use econometrics to explain the varying extents of convergence over time, space, and beverage type. (JEL Classifications: D12, L66, N10)